The role of stylistic devices in composition of conseptual integrity of a literary text - Rahmatova Sitora Samadovna,; Arustamyan Yana Yurievna, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract: This article investigates the pivotal role of stylistic devices in constructing and sustaining the conceptual integrity of literary texts. Conceptual integrity refers to the unified expression of a work’s central themes, ideas, ideological framework, and aesthetic vision, achieved through the deliberate interplay of linguistic and figurative elements. Stylistic devices—such as metaphor, simile, personification, repetition, alliteration, antithesis, and parallelism—function not merely as ornamental features but as structural mechanisms that ensure textual cohesion, coherence, thematic consistency, and emotional resonance. Drawing on qualitative stylistic and conceptual analysis of selected English and Uzbek literary works, the study demonstrates how these devices reinforce the author’s conceptual intentions, guide reader interpretation, and create a holistic artistic whole. By integrating theoretical frameworks from Western stylistics (e.g., Leech, Halliday) with Uzbek linguistic and literary scholarship, the research highlights the cross-cultural universality and national specificity of stylistic techniques in maintaining narrative and thematic unity. The findings underscore that stylistic devices are indispensable for transforming discrete linguistic units into a conceptually integrated literary artifact, offering valuable insights for literary analysis, translation studies, creative writing, and pedagogy.